Assessing village democracy and welfare in rural Indonesia: an index-based correlation analysis - Hakim, Lukman; Kolopaking, Lala M.; Sjaf, Sofyan; Kinseng, Rilus A. (Frontiers in Political Science, 2025)
Since the enactment of Village Law No. 6/2014, rural communities in Indonesia have gained greater autonomy, aimed at promoting democratic governance and enhancing rural welfare. However, village democracy still faces persistent challenges, including elite dominance, limited civic participation, and unequal access to welfare. This study examines the relationship between democracy and welfare within the theoretical framework of deliberative democracy, using a mixed-methods approach in three ecologically and politically distinct villages in West Java: Gelaranyar, Margahayu, and Pantai Bahagia. The Village Democracy Index, based on eight indicators, is analyzed alongside the People’s Welfare Index, which captures key dimensions of socioeconomic well-being. The findings indicate that rational and inclusive deliberation, as well as the fair application of procedural rules in village decision-making, lead to more responsive policies and equitable allocation of resources. These democratic processes are positively correlated with improvements in health, employment, and social protection. However, enhanced transparency and civil society engagement do not always translate into better infrastructure or environmental outcomes. These results underscore the importance of strengthening deliberative, participatory, and data-driven village governance to promote inclusive and sustainable rural development. Reforms must ensure that village deliberative processes go beyond procedural compliance toward data driven substantive democratic practices to achieve equitable welfare outcomes.